Gaya Kepemimpinan dan Fungsi Kelompok Tani dalam Budidaya Padi Sawah di Desa Jati Bali Kecamatan Ranomeeto Barat Kabupaten Konawe Selatan - Filda Miralda; Anas Nikoyan; Awaluddin Hamzah (Fakultas Pertanian Universitas Halu Oleo, 2022)
This study was motivated by the following phenomena occurred in Jati Bali Village that the chairperson who was delegated authority had injustice in the group. This happens because in the distribution of assistance from the government, the chairman prioritizes or prioritizes those who have family relations with him, so that farmers who do not have family relations with him have a little difficulty in receiving assistance on time, while the function of farmer groups as learning classes, vehicles for cooperation, and production units. not fully functioning, on the one hand it is applied but the intensity is still lacking, but on the other hand, from the three functions there are also those that are applied with a fairly frequent intensity. This is because farmers still do not feel they have a farmer group so that in forming a farmer group they only expect assistance from the government and the dependence of learning classes on extension workers. This study aims to determine the leadership style of farmer group leaders and the function of farmer groups in lowland rice cultivation in Jati Bali Village, West Ranomeeto District, South Konawe Regency. The number of informants in the study were 17 informants. Analysis of the data used in this study is a qualitative method which is processed using techniques according to Miles and Hubermen, namely data reduction and data presentation. The results of this study indicate that the dominant leadership style in each group is participatory leadership style, where the indicators of this leadership style are all fulfilled and the intensity is often applied, while the function of farmer groups in Jati Bali Village in lowland rice cultivation can be said to be less functioning.